Maximum recommended and allowable Radon-222 limits in water and air: Systematic review (Research, Society and Development, 2022)
Radon-222 is a radioactive gas that, when inhaled at high concentrations, can harm human health. However, there are several recommended and maximum allowable Radon-222 limits in water and air in the international community. Thus, this research aimed to evaluate the maximum recommended and allowed Radon-222 limits in drinking water and indoor air in the international community, indicating the most referenced organizations in Radon-222 studies through a systematic review. The results indicate that there is variation of up to 1000% between limits established for Radon concentrations in the air indicated by ICRP and US EPA. For water, the maximum limit established by EURATOM is 90 times higher than that established by US EPA. Greater relevance regarding the presence of Radon-222 in the air was also evidenced, due to its potential to detach from various physical means, such as water agitation, its occurrence in building materials and its release by contaminated soil. Finally, it was also found that the limits imposed by US EPA for the presence of Radon-222 in water and air were the parameters most used for comparison in the scientific community and that about 80% of evaluated studies reported from one two sources that proposed Radon-222 limits in air and water.